2012
DOI: 10.2220/biomedres.33.133
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Cimicifuga racemosa extract affects immobilization stress-induced changes in murine cerebral monoamine metabolism

Abstract: We investigated the effects of Cimicifuga racemosa (CR) plant extracts on the changes in levels of the cerebral monoamines norepinephrine (NE), dopamine (DA), and serotonin (5-HT), the respective metabolites 3-methoxy-4-hydroxyphenylglycol (MHPG), 3,4-dihydroxyphenylacetic acid (DOPAC), and 5-hydroxyindoleacetic acid (5-HIAA), and plasma corticosterone in mice subjected to acute immobilization stress. Single oral administration of the CR extract (1,000 mg/kg) significantly attenuated plasma corticosterone leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Several previous studies have reported that CR extract interacts with neurotransmitters such as 5-HT (6,32,39) and DA (5). In vitro, CR extract acts as agonist of various 5-HT receptors, particularly 5-HT 1A , 5-HT 1D , and 5-HT 7 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several previous studies have reported that CR extract interacts with neurotransmitters such as 5-HT (6,32,39) and DA (5). In vitro, CR extract acts as agonist of various 5-HT receptors, particularly 5-HT 1A , 5-HT 1D , and 5-HT 7 .…”
Section: Discussionmentioning
confidence: 88%
“…The stress-induced changes in murine cerebral monoamine metabolism (32). Although many clinical studies reported the efficacy of CR extracts for relieving menopausal symptoms, no investigations have been carried out into their anti-stress properties in humans.…”
Section: Methodsmentioning
confidence: 99%
“…Because certain extracts of Cimicifuga Racemosa are already recognized as safe and useful for the treatment of certain gynecological disorders [20,27], this study did not include an assessment of the safety of Remifemin; besides, due to the short duration of this experiment and the small number of animals, we were unable to observe the maximum effects of this drug. More studies are needed to fully elucidate Remifemin’s specific mechanisms that affect bone protection, and also regarding its optimal treatment duration and dosage for this additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Black cohosh, specifically, iCR has been shown to have an impact on brain via modulating neurotransmitter receptors in vitro [20][21][22][23] and in vivo in rodents [14,24] as well as in humans [25,26]. There is pharmacodynamic evidence for bioactivity of iCR-ingredients in brain in vivo, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…During menopause, the decline of circulating estrogens coincidences with the decline of brain bioenergetics and a shift towards a metabolically compromised phenotype [27]. Oral administration of iCR or E2 for 1 week to ovariectomized rats was able to restore neuronal excitability leading to functional recovery of hypothalamic activity [14,24]. Furthermore, iCR has been shown to upregulate genes related to cell survival under metabolic stress such as hypoxia [28][29][30].…”
Section: Discussionmentioning
confidence: 99%